2007
DOI: 10.1101/gad.447007
|View full text |Cite
|
Sign up to set email alerts
|

PRMT6-mediated methylation of R2 in histone H3 antagonizes H3 K4 trimethylation

Abstract: The arginine methyltransferase PRMT6 (protein arginine methyltransferase 6) has been shown recently to regulate DNA repair and gene expression. As arginine methylation of histones is an important mechanism in transcriptional regulation, we asked whether PRMT6 possesses activity toward histones. We show here that PRMT6 methylates histone H3 at R2 and histones H4/H2A at R3 in vitro. Overexpression and knockdown analysis identify PRMT6 as the major H3 R2 methyltransferase in vivo. We find that H3 R2 methylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
318
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(334 citation statements)
references
References 51 publications
12
318
3
1
Order By: Relevance
“…1; Couture et al 2006;Han et al 2006;Ruthenburg et al 2006;Schuetz et al 2006). Indeed, recent studies revealed that methylation of H3R2 by the PRMT6 methyltransferase impedes both H3K4 trimethylation and recruitment of WDR5 (Guccione et al 2007;Hyllus et al 2007). R2 is also important for the recognition of methylated K4 by CHD1 (Flanagan et al 2005).…”
Section: Wd40 Repeat Protein Structurementioning
confidence: 99%
“…1; Couture et al 2006;Han et al 2006;Ruthenburg et al 2006;Schuetz et al 2006). Indeed, recent studies revealed that methylation of H3R2 by the PRMT6 methyltransferase impedes both H3K4 trimethylation and recruitment of WDR5 (Guccione et al 2007;Hyllus et al 2007). R2 is also important for the recognition of methylated K4 by CHD1 (Flanagan et al 2005).…”
Section: Wd40 Repeat Protein Structurementioning
confidence: 99%
“…1,2 PRMT6 is a nuclear-localized RMT capable of creating omega-N(G)-monomethylarginine and asymmetric omega-N(G),N(G)-dimethylarginine derivatives on histone and other protein substrates containing a GAR motif; 3 it is the only RMT known to methylate the H3R2 mark. 4,5 This mark can act in opposition to the activating H3K4me3 mark, effectively acting as a transcriptional repressor. 6 PRMT6 has been reported to play a role in a variety of cellular processes including maintenance of stem cell pluripotency, 7 regulation of cell cycle, 8 DNA repair, 9 regulation of nuclear receptor-mediated transcription, 10 and viral transactivation.…”
mentioning
confidence: 99%
“…The role PRMTs play in cancer epigenetics remains unexplored, and it is essential to unravel how histone arginine methylation influences cancer. Previous studies have shown that the expression of EZH2, the catalytic subunit of PRC2/3, is altered in cancer cells (19,32,40,41). Similarly, several reports have shown that the interplay and cross-talk between chromatin-modifying enzymes is necessary for the efficient regulation of gene expression, and that changes that affect the activity and/or targeting of chromatin remodelers can trigger cancer (13, 23).…”
mentioning
confidence: 99%